Welcome to CEU
The longest edited version of the promotional video about the Central European University in Budapest. Established in 1991 and described as a pan-regional graduate university CEU was based upon British philosopher Karl Popper’s philosophical principle of an ‘open society’ and founded by financier and philanthropist George Soros. Contains information and images about students, faculty, management and affiliated institutions. The video starts with some remarks by István Teplán (Executive Vice- President) about CEU’s early history, the press, the Open Society Archives, and the CEU library. Mentioned as initiators of the idea of a Western-style university in Central and Eastern Europe and later, founders of CEU, are George Soros, Péter Hanák, Miklós Vásárhelyi, William Newton-Smith, Endre Bojtá, and Litván György. Interviews with CEU Faculty staff: Prof. Sorin Antohi (Academic Pro-Rector of CEU), Prof. János Kis (University Professor and Head of Political Science Department), Prof. William Newton-Smith (Member of CEU Board of Trustees, Board Member of the Roma Educational Fund, and Professor at Oxford University), Prof. Mária Kovács (Head of the Nationalism Studies Program), Prof. Dimitrina Petrova (Visiting Professor at the Legal Studies Department and founding Executive Director of The Equal Rights Trust think thank), Prof. Kim Lane Scheppele (Co-director, Gender Studies Program), Prof. András Sajó (University Professor and Founding Dean of Legal Studies at CEU, since 2008 judge at the European Court of Human Rights, Strasbourg), Prof. Tibor Várady (University Professor, International Business Law Stream), Prof. Gábor Klaniczay (Professor and Founding Head at the Department of Medieval Studies at CEU), Prof. László Bruszt (Political Science Department), and Prof. Ruben Mnatsakanian (Professor and Head of the Environmental Department at CEU). Students interviewed speak about the dormitory on Kerepesi street (The CEU Conference and Residence Center), the CEU library and the city of Budapest. Students are: Ainur Arenova (Legal Studies, Kazakhstan), Dziemidok Rafal (Human Rights, Poland), O Jong Su (International Cooperation Program, North Korea), Renáta Uitz (SJD Student, Legal Studies, Hungary), Angéla Kóczé (Roma Rights Course, Hungary), Iassen Deenitchin (Economical Sciences, Bulgaria), Mamuka Murijkneli (International Management Center, Georgia), Tamás Kozsik (Modeling Research Program, Hungary), Nikolai Vasilyev (Environmental Sciences and Policy, Russia), Katrin Kivimaa (Program on Gender and Culture, Estonia), Allan Simpson (Legal Studies, Scotland). In the final section, former US Ambassador to Hungary Donald Blinken (First CEU Chancellor) speaks about the university and its purpose. Excerpts from various interviews with George Soros (Founder of CEU and Chairman of the Board of Trustees) are available on this tape.